Patterns of timber harvesting and its relationship with sustainable forest management in the western Amazon, Ecuador case - Bonilla-Bedoya, Santiago (2017)
The Amazon rainforest lies within the most diverse forest ecosystem in the world. However, a large part of the tropical rainforest is being degraded because of timber harvesting without any sustainability criteria and owing to a limited understanding of the effects of forest exploitation. The Ecuadorian Amazon (EA) is part of the Andes Amazon (AA), an area covered by five countries (Venezuela, Colombia, Ecuador, Peru and Bolivia). This research identified the patterns of legal timber harvesting in the EA and determined current trends with respect to mostly harvested forest species. Two harvesting programs aimed at small farmers prevail in the EA: first, naturally regenerated trees felling program, and simplified timber harvesting programs in native forests. Considering the surface and volume of logging, significant differences were detected between logging procedures and ecosystems in the region. Two hundred and thirty-two genera are registered for harvest and, 51.93% of the total harvesting volume comes from eight genera and ten species. This research shows that in fallows of fragmented forest ecosystems, small farmers are harvesting fast-growing pioneer species. Maintaining a sustainable production in timber harvesting depends, by and large, on the harvesting and felling programs established on small farms. © 2017 Taylor & Francis.